Accuracy of Deep brain stimulation (DBS) lead Placement: A Comparative study of bilateral and Four-Lead implantation Techniques - Patrick Fricke; Cordula Matthies; Vera Nickl; Maria Breun; Martin M Reich; Robert C Nickl (Interdisciplinary Neurosurgery)
Objective: Deep Brain Stimulation (DBS) is an established treatment modality for various movement disorders and psychiatric conditions. The effectiveness of DBS largely hinges on the precise placement of electrode leads. However, inaccuracies in electrode positioning can lead to reduced treatment efficacy and adverse side effects. Methods: 52 patients with 128 leads, (40 patients, in the bilateral group with 80 leads & 12 in the four-lead group with 48 leads) who received DBS implantations with MER-recordings at the University Hospital of Wuerzburg between 2013 and 2019 were reviewed. Preoperative planning and postoperative imaging were assessed for lead placement accuracy. Clinical outcomes, surgical sequelae, and stimulation parameters were evaluated through patient records. Results: The bilateral group exhibited a mean radial deviation of 1.40 mm from the planned trajectory, with a significant difference in accuracy between the first and second implanted leads. In the four-lead group, while there was an increasing trend in deviation between the first and the fourth electrode, it was not statistically significant. Conclusions: This study contributes novel insights into the complexities of implanting multiple leads in a single DBS session. It highlights the importance of minimizing brain shifts during surgery to improve lead placement accuracy. The findings recommend prioritizing the implantation of the most clinically significant lead first, given the observed decrease in placement accuracy for subsequent leads or a staged procedure. The study represents the largest systematically assessed cohort analyzing electrode placement accuracy in four-lead DBS procedures to date.